Analysis of Promotion Strategies Through Advertising Media in Increasing Consumer Loyalty - Rahmaida Sophia Veronika Mendrofa; Maria Magdalena Bate’e; Eduar Baene; Yuterlin Zalukhu (Golden Ratio of Data in Summary, 2024)
UD. Talenta faces several weaknesses in marketing catering services, such as a lack of diversification in promotional methods which still rely on traditional methods and word of mouth, which limits market reach. In addition, limited access to technology and the internet hinders the use of digital platforms for promotions, while increasingly tight competition with similar competitors causes difficulties in distinguishing ourselves, so that sales levels experience fluctuations, especially in the midst of unstable economic conditions. This research uses a qualitative approach with methods. field study. Data collection techniques were carried out by means of interviews, observation and documentation using the Milles and Huberman data analysis approach. The research results showed that UD. Talenta relies on marketing strategies that include promotion through social media, print, word of mouth recommendations, and local event participation to expand the reach of its services. Despite facing resource constraints and intense competition, advertising strategies, especially on social media, are considered quite effective in expanding the market and increasing consumer loyalty. Promotional effectiveness is influenced by message clarity, visual appeal, and brand image consistency, although challenges remain in maintaining customer loyalty and overcoming budget constraints. UD. Talenta continues to innovate and evaluate strategies to improve its advertising campaigns. To strengthen consumer loyalty, UD. Talenta need to focus on clarity of information in advertisements, as well as improving the consistency and quality of advertisements with content innovation that is creative and relevant to consumer needs.